3PC-029 Paediatric drug resistant epilepsy: nitrazepam 1 mg/mL solutions to avoid clinical therapeutic error. (24th March 2020) - Berardi, MA; Ortenzi, GB; Moretti, V; Adresciani, E; Garzone, AMF; Cappanera, S; Polidori, C; Pompilio, A
Abstract : Background and importance: The management of paediatric patient with drug resistant epilepsy (EDR) is complicated and often requires therapy and dose adjustments. The clinical pharmacist and child neuropsychiatry unit cooperate to prevent clinical therapeutic errors, common in the prescription of drugs with reduced and personalised dosages. Nitrazepam (NTR) in children is recommended in epileptic spasms, in Dravet, West and Lennox–Gastaut syndromes. There is a probable risk of administration error due to the low prescribed dosage (125 µg/kg) 1 and crushing of commercial tablets. Aim and objectives: To make a liquid formulation with a standard concentration, easily adaptable to paediatric needs as weight changes, that is palatability, suitable and simple to use during hospitalisation and at home. Material and methods: Multiphase study: Phase I: data collection. Retrospective study examined the medical records of children born 2008–2019 with a certain diagnosis of EDR: patient number, sex, age, epilepsy classification according to the International League Against Epilepsy criteria, 2 antiepileptic therapy and dose of drug were collected. Phase II: subject study of nitrazepam, its dosage and the galenic compounding formulation it was possible to use. Phase III: chemical–physical–microbiological stability analysis of nitrazepam 1 mg/mL. Samples were stored for 30 days at 2–8°C and/or ambient at 25°C. Chemical–physical stability was measured by quantitative determination of the molecular ions of nitrazepam C282.1/C236, using high pressure liquid chromatography (HPLC), equipped with a UV detector, interfaced with a triple quadrupole mass detector (mass spectrometer, MS/MS), column Luna C1850 mm, standard nitrazepam D5 100 µg/mL. 3 Microbiological stability was assessed according to the Italian Ufficial Farmacopea (FUI). 4 Results: A total of 101 children with EDR (54 males, 47 females) were studied, aged mainly 3–4 years (20%) and 9–10 years (33%). Classifications: focal onset in 34.86%, focal to bilateral tonic–clonic in 17.10%, generalised onset in 47.36% and unclassified in 0.65%. Thirty-one drugs are prescribed, the most used were: levetiracetam (27%), clobazam (25%), topiramate (21%) and NTR (12%). Required dosages of NTR difficult to administer: 0.625 mg, 0.83 mg, 1.25 mg, 1.66 mg and 2.5 mg. Three liquid galenic formulations were set up (NTR from Mogadon 5 mg tablets): NTR 1 mg/mL simple syrup methylcellulose 1%, NTR 1 mg/mL suspension tragacanth gum and NTR 1 mg/mL Syrspend SFAlkaDry. 5 HPLC MS/MS analysis confirmed uniform and steady dosage, and 30 day stability for NTR 1 mg/mL suspension and NTR 1 mg/mL Syrspend SFAlkaDry. Conclusion and relevance: Good clinical practice and collaboration between departments allowed better management of epileptic seizures in children affected by severe EDR. Reproducible and safe therapy means improving patient's life and therapeutic compliance. References and/or acknowledgements: 1. British National Formulary for Children 2014 2. https://www.ilae.org/files/ilaeGuideline 3. https://www.sigmaaldrich.com 4. Farmacopea Ufficiale Italiana XII ed. 5. https://fagron.com/en/product/syrspendr-sf-alka-dry No conflict of interest.